Unusual Case of Foreign Body Ingestion in a Child: A Case Report - Nag, Suresh Kumar (Journal of Nepalgunj Medical College, 2021)
Foreign body ingestion is a common problem in pediatric age group patients throughout the world. Radiographic findings revealed multiple foreign bodies throughout abdomen. Foreign objects attach frequently at the esophageal anatomic narrowing. They must be taken out immediately because they can cause an obstruction, mucosal erosion or perforation. Endoscopy is the criterion standard for removal of foreign bodies from the esophagus. Here, we report an interesting case of a multiple stones ingested by a female child. The child presented with complaints of distension of abdomen, vomiting and pain all over abdomen. The foreign bodies were found as hard black stones after removing them through anal route.